Classification of non-Q-wave myocardial infarction according to electrocardiographic changes. Issue 5 (November 1985) - Ogawa, H; Hiramori, K; Haze, K; Saito, M; Sumiyoshi, T; Fukami, K; Goto, Y; Ikeda, M
Abstract : The characteristics of 93 patients in whom electrocardiographic recordings were obtained within 12 hours of the onset of non-Q-wave myocardial infarction were studied. Patients were divided into the three groups according to what electrocardiographic changes were seen. Forty nine patients had ST segment depression, 35 had ST segment elevation, and nine had T wave changes. Patients with ST segment depression had a higher rate of pump failure and multivessel disease than the other two groups. There were no significant differences in peak serum creatine kinase activity among the three groups. Twelve of 13 patients who died of non-Q-wave myocardial infarction in hospital had ST segment depression. Furthermore nine of them had attacks of non-Q-wave myocardial infarction with severe ST segment depression in many leads. At necropsy five of six patients who had shown severe ST segment depressions in many leads at the onset of non-Q-wave myocardial infarction were found to have circumferential subendocardial lesions with triple vessel disease. This study suggests there are electrocardiographic subtypes of non-Q-wave myocardial infarction that are associated with specific patient characteristics.